Ratio Legis Hukum Perjanjian Jual Beli E-Commerce - dahris Siregar (Universitas Slamet Riyadi, 2023)
Almost the last ten years, a phenomenon has occurred and changed almost all aspects of life, especially in terms of transactions. Some people, especially business people, consider this phenomenon as a solution. One proof of the superiority of this technology is the ability of technology to easily transform conventional payment systems (cash) that have survived for centuries into electronic payment systems (cash). In the end, people are accustomed to using technology to run the trading system. The author conducts literature research or institutional research with normative juridical methods. The main data sources used are laws and court decisions. Secondary legal materials consist of literature, expert opinions, legal dictionaries, and law and economics books. The implications of this investigation are; The government should establish a legal entity to supervise and select shop or website owners to reduce crime, especially the crime of buying and selling online. Legislation related to electronic information and transactions should also be developed to protect sellers and buyers. People who use the internet should exercise caution when using computers or other electronic devices connected to the internet to buy or sell goods over the internet. The site must be clear and reliable, with clear agreements or contractual conditions and not mutually harmful.